SISTEM INFORMASI TUMBUH KEMBANG ANAK USIA DINI DI TK HARAPAN BUNDA BERBASIS WEBSITE - Tedjo Darmanto; Khoirida Aelani; Moch Alvy Nuryasinda (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2025)
Early childhood education is crucial for laying the foundation of a child's cognitive, social, and emotional development. However, many educational institutions face challenges in managing child development data effectively. In an effort to address this issue, TK Harapan Bunda has developed an information system that can monitor child growth and development in real-time. This web-based system features a user-friendly interface to facilitate data input and information access for users. The method used in the development of this system is Object-Oriented Programming (OOP), which includes the stages of requirements analysis, design, development, testing, and implementation. With the implementation of the child growth and development information system at TK Harapan Bunda, it is expected to improve the quality of education and provide better support for early childhood development. This system not only assists in data management but also strengthens communication between the school and parents.